Nutritional value and health-promoting properties of Agaricus bisporus (Lange) Imbach - Golak-Siwulska Iwona; Kałużewicz Alina; Wdowienko Siergiej; Dawidowicz Luiza; Sobieralski Krzysztof (Herba Polonica, 2018)
The white button mushroom Agaricus bisporus (Lange) Imbach is an edible mushroom of top economic significance. In recent years the consumption of fruiting bodies of this species has been increasing in Poland. The article characterises the chemical composition and health-promoting properties of white button mushrooms. The latest scientific research confirms that the fruiting bodies of white button mushroom have high nutritional value. They contain good quality proteins, necessary unsaturated fatty acids, fibre, some vitamins and numerous minerals. Apart from that, white button mushroom fruiting bodies contain a wide range of bioactive substances, which have a positive influence on health, such as polysaccharides, glyco-proteins, tocopherols, polyphenols and other antioxidants, e.g. ergothioneine. Apart from the antioxidant properties, the white button mushroom also has anti-inflammatory, antimicrobial, antifungal, anticancer, immunomodulatory, hepatoprotective and anti-atherosclerotic activities.